Background From The Government Of Malaysia For Giving Amnesty To Indonesian Illegal Labor In Malaysia During 2002-2009 - Farida Suldina (Syntax Idea)
For Indonesia, international migration was an interesting phenomenon in overcoming labor problems of employment crisis. In addition to obtain benefits of remittance from sending productive age workers abroad, the Government can solve the problem of unemployment. Based on the cclassification, the encouraging factors for labors to migrate were divided into three categories, including demand pull, supply push and network factors. Indonesian workers in Malaysia, however, did not comply with the immigration law, that required them to arrange for work permits to be allowed to work in Malaysia, which they did not make, or the validity period was not extended. As a cconsequence, they became illegal. But due to high demand of workers needed by Malaysian capital owners, they asked the Government to issue an amnesty, so that their businesses would not stop or go out.